Increasing Elementary School Children's Knowledge about Health Education Related to PHBS at SD N 3 Bulukarto - Fatma Riyanti, Nia; Ghariza, Afif; Hediya Putri, Riska; Yudi Ismanto, Amatus (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The coverage of Clean and Healthy Living Behavior (PHBS) at SDN 3 Bulukkarto is still low, and only a few students apply it. Therefore, it is important to improve the knowledge of elementary school students through health education related to PHBS. With PHBS, it is expected that the community will be able to recognize and overcome health problems independently and implement a healthy lifestyle by maintaining, maintaining and improving their health. This study aims to analyze the effect of PHBS education on the knowledge of primary school students at SDN 3 Bulukkarto. Method: The research method used a pre-experiment design with a one group pretest-posttest design, involving 30 respondents selected through total sampling. Data were collected using a questionnaire and analyzed using the Wilcoxon test. Result: The results showed an increase in the median value of respondents' knowledge from 73.00 (pre-test) to 86.00 (post-test), with P-value = 0.000 (p < 0.05). Conclusion: It is recommended that the government continue to hold PHBS education regularly and utilize social media to increase children's knowledge.